Tangled up in text: tefillin and the ancient world - Cohn, Yehudah (Brown Judaic studies, 2008)
Deuteronomy to Alexander (seventh century B.C.E. to 331 B.C.E.) -- Tefillin in the later Second Temple period -- The Tannaʼitic era (70 C.E. to the third century) -- In conclusion, the meaning of the Tefillin ritual